Cultural development of Sharjah and its heritage institutions - AlTunaiji, Saeed; Aboushouk, Mohammed (Al-Adab Journal, 2024)
The Emirate of Sharjah was known as the cultural capital of the United Arab Emirates, thanks to the efforts made in large sectors of the emirate, especially in the cultural and tourism sector, those efforts led by Sheikh Dr. Sultan Al Qasimi, Member of the Supreme Council of the United Arab Emirates, Ruler of the Emirate of Sharjah, culminated in placing the emirate in a great position nationally, locally, Arab, and international, especially in terms of tourism and culture. These efforts were not only for the benefit of the Emirate of Sharjah, but also extended to many areas of the country and other Arab regions. Hence, this study aims to address the cultural development of the emirate and its cultural institutions and its reflection on the cultural tourism sector in the emirate, as it deals with the cultural and heritage institutions that have been established in the emirate and its historical development and its role in enriching cultural life and building a cultural identity for the Emirate of Sharjah, as well as focusing on Sheikh Sultan’s interest in developing the emirate’s resources and harnessing them with the aim of promoting the cultural and tourism sector over half a century.